Qualifizierungsstrategien deutscher Unternehmen in Japan, Indien und China - Deutsche Vorbilder oder einheimische Verfahrensweisen? - Burgt, Jochen van der [Verfasser]; Li, Junmin [Verfasser]; Wilbertz, Christine [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2014)
"For many years the possible introduction of the German dual vocational education programme into other countries has been discussed. The transferability of the German vocational education and training system into other countries has been controversially discussed in the work of development assistance and in international comparative vocational education research for a long time, even though the empirical basis is quite narrow. The present study focuses on the vocational and training behaviours of German corporations in their subsidiaries in Japan, China and India. Even though all three nations are important countries for the German corporations the culture, the vocational education and employment systems are very different. Based upon the theory of the EPRG model in international management, this study analyses the vocational education and training activities and in terms of the EPRG model by interviews with experts. The findings indicate that a polycentric approach is used exclusively in India and to a significant extent in China. In Japan, in addition to the prevalent polycentric approach, there is also a strong influence of geocentric training styles. The similarities can be partly explained by the stronger focus on theoretical training institutions and a more academic attitude in society as a whole, which means that purely vocational training plays a marginal role with low esteem. In this context, it would be difficult to implement the German style of vocational education and training." (Authors' abstract, BIBB-Doku)

"Seit Jahren ist die Einführung dualer Ausbildungsgänge nach deutschem Vorbild in anderen Ländern ein aktuelles Thema. Die Übertragung des deutschen Berufsbildungssystems wird allerdings in der Entwicklungszusammenarbeit und im Rahmen der international vergleichenden Berufsbildungsforschung bereits seit Jahren auch kontrovers diskutiert, wobei empirische Befunde nur rudimentär vorliegen. In der hier vorgestellten Studie wird das konkrete Qualifizierungsverhalten deutscher Unternehmen in ihren Auslandsstandorten in Japan, Indien und China untersucht. Basierend auf dem theoretischen Zugang der EPRG-Typologie der internationalen Unternehmensführung wird durch Experteninterviews in den drei Ländern untersucht, wie sich die jeweiligen Qualifizierungsmuster darstellen und einordnen lassen. Die Befunde weisen darauf hin, dass in Indien ausschließlich und in China maßgeblich eine polyzentrische Strategie verfolgt wird. In Japan findet sich, neben der auch dort vorherrschenden polyzentrischen Ausrichtung, hingegen ein Einfluss geozentrischer Ausrichtungen der Qualifizierungsstile. Die Gemeinsamkeiten lassen sich teilweise über ein theoretisch ausgerichtetes Schulsystem und ein akademisch fokussiertes Gesellschaftsbild erklären, welche der beruflichen Bildung nur eine marginale bzw. stigmatisierte Rolle zuweisen. In diesem Kontext kann eine berufliche Ausbildung deutscher Prägung nur schwer realisiert werden." (Autorenreferat, BIBB-Doku)
Vocational and training behaviours of German corporation in Japan, India and China - German models or local procedures?
Keywords: S 1.1 Allgemeinbildende Schule; S 1.3.1 Ausbildung im Dualen System; I 2.3.4 Asien; Fachkräftequalifizierung; Berufsbildungssystem; Transfer; Japan; Indien; China